Character Building for the Young Generation Through Kompangan Arts in Mendalo Indah Village, Jambi - Kuswanto Kuswanto; Muhammad Ali Hasan Al Banna (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This program aims to reconstruct youth character and reduce consumer gadget addiction by integrating traditional Kompangan arts with digital technology Research Methodology: Conducted in Mendalo Indah Village, Jambi, this quantitative study involved 15 youths purposively sampled using a One-Group Pretest-Posttest design. Primary data were collected via a Google Forms questionnaire. The intervention involved training in the Kompangan interlocking rhythm ensemble. Data were analyzed using the Shapiro-Wilk test and Paired Samples T-Test via SPSS. Results: Evaluations indicated significant character improvements. The Paired Samples T-Test showed a significance value of 0.000 (p < 0.05), with average scores increasing from 57.50 to 75.17. Discipline, responsibility, and cooperation were in the high category, while love of culture was in the very high category. Conclusion: Digitally adapted Kompangan art is an effective pedagogical tool. It successfully transformed youth behavior, breaking the cycle of gadget-induced individualism and fostering collective rhythmic commitment. Limitations: The study is limited by a small sample size (15 youths), a lack of longitudinal post-program monitoring, and the absence of specific psychometric instruments to quantitatively assess reductions in gadget addiction. Contribution: Practically, this study serves as a reference for village governments in developing youth policies. Academically, it enriches literature in the sociology of art, social pedagogy, and cultural studies regarding local wisdom preservation.